Endothelial Cell Dynamics in Vascular Development: Insights From Live-Imaging in Zebrafish - Okuda, Kazuhide S.; Hogan, Benjamin M. (Frontiers in Physiology, 2020)
The formation of the vertebrate vascular system involves the acquisition of endothelial cell identities, sprouting, migration, remodelling and maturation of functional vessel networks. To understand the cellular and molecular processes that drive vascular development, live-imaging of dynamic cellular events in the zebrafish embryo have proven highly informative. This review focusses on recent advances, new tools and new insights from imaging studies of vascular cell biology using zebrafish as a model system.